Unilateral vesicoureteric reflux: Low prevalence of contralateral renal damage - Polito, Cesare; Rambaldi, Pier Francesco; Mansi, Luigi; Di Toro, Rosario; La Manna, Angela (The Journal of pediatrics, 2001)
Objective: We assessed the risk for the occurrence of renal damage in children with vesicoureteric reflux (VUR). Study design: We reviewed the records of 187 consecutive children, aged 3.8 ± (SD) 2.8 years, with unilateral primary VUR diagnosed after urinary tract infection (UTI). Dimercaptosuccinic acid renal scintigraphy was performed 4 to 6 months after the last UTI. Three patterns of renal damage were identified: global reduction (GR) of renal radionuclide uptake (20% to 40% of relative uptake), focal defects (FD) in uptake, and shrunken (relative uptake <20%) kidney (SK). We assumed that in these subjects FD indicated postpyelonephritic damage and that GR indicated congenital renal damage. Results: Scintigraphic renal damage of any type was present in 36.9% of the refluxing and in 3.2% of the nonrefluxing kidneys (odds ratio [OR], 17.6; 95% CI, 7.4 to 41.9). FD were present in 15.5% and 2.7% (OR, 6.7; CI, 2.5-17.6), GR in 19% and 0.5% (OR, 44.3; CI, 6.1 to 327.2), and SK in 6.9% and 0%, respectively. Patients with severe VUR showed a higher probability of renal damage than those with nonsevere VUR. Conclusions: In children with UTI and VUR, the refluxing kidney is most at risk of both congenital and acquired renal damage, and this risk increases with severity of reflux. (J Pediatr 2001;138:875-9)